Silat Pangean as the Cultural Identity of the Terusan Village Community, Maro Sebo Ilir District, Jambi - Mardius, Ali; Barlian, Eri; Ahmadi, Ahpan; Kumar, Alfiqroam; Utama, Jaka Putra (Universitas Majalengka, 2024)
One of the traditional cultural legacies with significant historical and philosophical significance in the life of the people of Terusan Village, Maro Sebo Ilir District, Jambi Province, is Silat Pangean. Examining Silat Pangean's importance as a local community's cultural identity, comprehending its values, and evaluating attempts to maintain this heritage in the face of modernization are the objectives of this study. Through documentation studies, in-depth interviews, and interactive observation, a qualitative ethnographic research methodology is employed. The study's findings demonstrate that Silat Pangean serves as a tool for cultural expression, character development, and social cohesion in addition to being a martial art. Among the virtues embodied in Silat Pangean are integrity, self-control, bravery, and reverence for ancestors' customs. However, the younger generation's lack of interest and changes in people's lifestyles pose difficulties to this institution. Regular training, incorporation into customary practices, and promotion through cultural festivals are all part of conservation initiatives. To sum up, Silat Pangean is a representation of cultural identity that needs to be maintained in order to preserve the Terusan Village community's traditional knowledge. To ensure that this tradition endures and is relevant in the future, support is required from a variety of sources, including the government, local authorities, and the younger generation. cultural identity, Terusan Village, preservation of tradition, local wisdom